ASPECTS OF THE CHINESE REGIONAL CULTURE IN THE CITY VISUAL IMAGE DESIGN (BASED ON THE LOGOS OF THE SHANDONG PROVINCE CITIES) - LI, X.; Skliarenko, N. (Art and Design, 2024)
The purpose of the study is to identify aspects of regional culture in the formation of the design of the visual image of the city based on the logos of the cities of Shandong Province. Methodology. The research approach is interdisciplinary, which serves as the basis of the study and helps us to analyze the city logo more comprehensively. The semantic analysis method is used to reveal the deeper meaning of city logos and elaborate the narrative strategy, which can focus on the overall content of the city and reflect the city's identity. The method of art criticism allows us to evaluate the visual characteristics and design elements of city logos in order to refine visual elements that correspond to the essence of their image. The article analyses the logo image cases of 12 cities in Shandong Province, which are different in terms of development scale and regional environment, and can effectively demonstrate regional characteristics of Shandong Province and reflect its cultural diversity. Results. The article presents aspects of regional culture as a basis for city visual image design of Shandong Province, which play an important role in creating the city's logo image. The following regional features are highlighted – traditional symbols, historical architecture and natural environment, which define the concept of the city's cultural development. The combination of text and graphic elements and appropriate colours ensures that the cultural connotations of the region are integrated into the creation of the city logo. The attention to the regional aspects helps to improve the overall image of the city and strengthen the brand influence of the city, thus realising the sustainable development of the city and showing the direction for the future development of the city. Scientific novelty. The article reveals the role of regional culture in designing a city's visual identity, specifically through the lens of a city logo image, for the first time. In general, Regional culture emphasises uniqueness of the city's identity, which is often based on local city history, culture and social customs, and subject to the constraints of time and space, which has a dynamic character, and becomes a positive force for the development of the city and reflects its connotative characteristics through the design way. This has resulted in a more visually appealing logo image that incorporates regional cultural characteristics into the design of the city's visual image. Practical significance. The analysis of visual forms embodied on the basis of the regional characteristics of the cities of Shandong Province can help practicing designers in developing the visual identity of the city environment. Traditional symbols, historic architecture and the natural environment provide new research ideas for restoring a harmonious image of the city that combines regional cultural characteristics and artistic expressions. The city logo is updated over time, and this idea can be widely used in a variety of design practices. The research is important for the development of the methodology for designing the visual image of the city. It has been proved that the exploration of regional culture in city logo design can enhance the value, competitiveness and development level of the city.